Learning Curve of Microendoscopic Discectomy in Single-Level Prolapsed Intervertebral Disc in 120 Patients. Issue 5 (August 2020) - Jain, Sanyam; Merchant, Zahir; Kire, Neil; Patel, Jwalant; Patel, Ankit; Kundnani, Vishal
Study Design: Retrospective study of prospectively collected data. Objective: To evaluate learning curve of tubular microendoscopic discectomy (MED) in lumbar prolapsed intervertebral disc (PIVD) patients based on surgical and clinical parameters and delineate the challenges faced in early cases while practicing MED in large series of patients. Methods: This study was an institutional review board–approved retrospective study of the first 125 consecutive patients with single-level lumbar PIVD managed with tubular MED from 2008 to 2016 with a minimum 2-year follow-up. A total of 120 patients available at final follow-up were divided into quartiles (30 each) as per the date of surgery, with each consecutive group serving as a control for the previous group. Preoperatively and postoperatively clinical parameters (pain scores [Visual Analogue Scale; VAS], functional disability [Oswestry Disability Index; ODI] score, modified MacNab criteria), perioperative parameters (operative time, blood loss, hospital stay), technical issues (guide wire migration, tube docking–related problems, dural tear), and postoperative complications (postoperative leg pain, neural injury, infection, recurrence) were evaluated. Statistical analysis—logarithm curve-fit regression analysis and ANOVA test. Results: The sample consisted of 75 males and 45 females (mean age: 42.54 years) with no significant difference among the quartiles. There was significant difference ( P < .005) noted in mean operative time (quartile 1, 87.33 minutes; quartile 2, 58.5 minutes) and mean blood loss (quartile 1, 76.33 mL; quartile 2, 32.66 mL) between quartile 1 and quartile 2, with no further significant reduction in quartile 3 and quartile 4. Significant difference ( P < .005) in clinical parameters (VAS preoperative/postoperative 5.28/0.99; ODI preoperative/postoperative 32.18/12.08) were noted but was not associated with surgical experience. Overall, 90% (108 out of 120) of the patients had good to excellent results according to the modified MacNab criteria. The mean hospital stay did not show any significant difference among the quartiles. Guide wire migrated issues, neural injury, dural tear, and tube docking–related problems were significantly reduced after quartile 1. However, recurrence occurred at any phase. Infection occurred in one patient in quartile 1. Although blood loss and operative time showed a declining trend, it was not significant after quartile 2. So asymptote lay in quartile 1 and we recommend that novice surgeon should perform 25 to 30 cases to achieve mastery in this technique. Conclusion: For mastering the art of tubular MED for lumbar PIVD and to reduce its learning curve, novice surgeons can avoid the challenges and problems faced during initial cases with improvement in surgical skills by practicing on cadavers, wet labs, and bone-saw models following certain recommendations that we have after achieving asymptote. Familiarity with instrumentation, communication between surgical team, and defined expectations from radiology technicians are key to reduce the learning curve.